2020
DOI: 10.1080/22221751.2020.1825914
|View full text |Cite
|
Sign up to set email alerts
|

Short- and potential long-term adverse health outcomes of COVID-19: a rapid review

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has resulted in millions of patients infected worldwide and indirectly affecting even more individuals through disruption of daily living. Long-term adverse outcomes have been reported with similar diseases from other coronaviruses, namely Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). Emerging evidence suggests that COVID-19 adversely affects different systems in the human body. This review summarizes the current evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
142
0
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(162 citation statements)
references
References 82 publications
2
142
0
18
Order By: Relevance
“…2 Older adults and those with underlying heath conditions are particularly susceptible to severe outcomes; however, recent evidence suggests that even mild COVID-19 may result in prolonged symptoms and/or long-term adverse health outcomes. 3 The pandemic has carried a substantial economic burden globally, 4 and several countries have experienced unprecedented rise in demand on healthcare systems far exceeding capacity to respond. 5 There remain limited effective interventions to treat COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…2 Older adults and those with underlying heath conditions are particularly susceptible to severe outcomes; however, recent evidence suggests that even mild COVID-19 may result in prolonged symptoms and/or long-term adverse health outcomes. 3 The pandemic has carried a substantial economic burden globally, 4 and several countries have experienced unprecedented rise in demand on healthcare systems far exceeding capacity to respond. 5 There remain limited effective interventions to treat COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [ 32 ] showed an association between reduced insulin sensitivity and lower ACE2 that might be of high interest. Hyperglycemia is commonly noticed in COVID-19 disease [ 40 ] and poorly controlled glucose metabolism increases the seriousness and mortality in diabetic patients with COVID-19 [ 41 , 42 , 43 ]. With fatigue presenting as a common symptom of both diabetes and COVID-19, having both may exacerbate the occurrence of fatigue and lead to poorer long-term outcomes.…”
Section: Factors Contributing To Post-covid-19 Fatiguementioning
confidence: 99%
“…However, the clinical relevance of thyrotoxicosis associated with SARS-CoV2 infection is still controversial [3,14,15,4] and data on the outcome of thyroid function after remission of COVID-19 are scanty [14]. Speci cally, it is still unknown whether thyroid gland may be persistently damaged by SARS-CoV2, such as demonstrated for other tissues and organs in individuals with COVID-19 [16].…”
Section: Introductionmentioning
confidence: 99%